The development of georeferencing technique for conversion of existing topographic data to new geocentric-based datum - Omar, Abdullah Hisam; A. Kadir, Abd. Majid; Ses, Sahrum (Universiti Teknologi Malaysia, 2003)
In LIS, the most important core datasets to support spatial component are the cadastral and topographic datasets. Cadastre (DCDB) and topographic (DTDB/CAMS) datasets were used in this study are from different coordinates system, sources, accuracy and differing government agencies, and it post a number of problems to integrate. In order to integrate, several issues must be considering, which are data structure, data quality, reference system and GIS environment. Geocentric RSO coordinate system was adopted as reference system in this study. The cadastral dataset NDCDB that obtained has been geo-referenced, namely NDCDB. Thus this research was more focused on georeferencing DTDB/CAMS dataset to establish NDTDB dataset, with purpose of integration. There are two methods of georeferencing, polynomial and datum transformation.